2013
DOI: 10.1148/radiol.13122089
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Metal Artifacts from Hip Prostheses on CT Images of the Pelvis: Value of Iterative Reconstructions

Abstract: The IFS algorithm for CT image reconstruction significantly reduces metal artifacts from hip prostheses, improves the reliability of CT number measurements, and improves the confidence for depicting pelvic abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
98
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(107 citation statements)
references
References 22 publications
7
98
0
2
Order By: Relevance
“…IMAR reduced metal artifacts significantly and improved number measurements with CT and the confidence in depicting pelvic abnormalities. 21 In our study, we found a significant improvement in softtissue delineation in the oral cavity and oropharynx, but we also found a degradation of bone delineation; artificial defects in the IMAR datasets of the bone abutting the metallic implants appeared in a number of cases (58%). Because of the reduction of streak artifacts, however, a better delineation of cortical bone at more remote areas in the sections containing metal hardware was achieved.…”
Section: Discussionsupporting
confidence: 56%
“…IMAR reduced metal artifacts significantly and improved number measurements with CT and the confidence in depicting pelvic abnormalities. 21 In our study, we found a significant improvement in softtissue delineation in the oral cavity and oropharynx, but we also found a degradation of bone delineation; artificial defects in the IMAR datasets of the bone abutting the metallic implants appeared in a number of cases (58%). Because of the reduction of streak artifacts, however, a better delineation of cortical bone at more remote areas in the sections containing metal hardware was achieved.…”
Section: Discussionsupporting
confidence: 56%
“…Since image noise is reduced compared to the traditional filtered back projection (FBP) reconstruction method, IR can be used in the clinical setting with two different major aims: firstly, to achieve reduction of patient dose exposure by reducing the exposure settings; secondly, to achieve a possible improvement in image quality by reduction of image noise and beam hardening artifacts [8 -18]. Other possible fields of applying IR include e. g. reduction of metal artifacts or scatter compensation, which may become even more important in the future [19,20]. Some recent studies have sought to demonstrate a potential effect of IR techniques in brain CT [8, 17,21].…”
mentioning
confidence: 99%
“…To more practically reduce segmentation errors, Prell et al [45] suggested tissue classification on a CT image corrected by linear interpolation. This idea has recently motivated some recent attempts to iteratively improve the derivation of the prior image [61], [62]. There are also other approaches enabling to avoid segmentation errors and possibly to improve the accuracy of recovered projections by defining a prior image from statistical anatomical atlases [63].…”
Section: Discussionmentioning
confidence: 99%